2023
DOI: 10.3390/app13095678
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanical Characteristics and Ground Surface Settlement Influence of the Rise–Span Ratio of the Pile–Beam–Arch Method

Abstract: The pile–beam–arch method (PBA) method is increasingly being used in the construction of metro stations with complex traffic conditions. The rise–span ratio of the arch not only affects the height of the station, but also affects the rationality of the design of subway stations and the safety of construction. The mechanical response of steel pipe piles with different rise–span ratios and the effect of controlled surface settlement have been investigated in the interactions involved in pile–soil system. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In the study of the existing hole pile method [8,32], it was found that the excavation of the guide hole was the main construction stage that caused the surface settlement. Controlling the settlement of the guide hole is conducive to controlling the settlement of the subsequent construction process.…”
Section: Simulation Of Construction Stagementioning
confidence: 99%
“…In the study of the existing hole pile method [8,32], it was found that the excavation of the guide hole was the main construction stage that caused the surface settlement. Controlling the settlement of the guide hole is conducive to controlling the settlement of the subsequent construction process.…”
Section: Simulation Of Construction Stagementioning
confidence: 99%
“…The side pile transmits the load of the upper soil to the deep soil and is vital in limiting the deformation of the station. The previous research on metro stations with PBA method mostly focused on the control of surface settlement and the optimization of the excavation method (Wang and Guo 2016;Yu et al 2019;Li and Chen 2020;Guo et al 2021;Lv et al 2023). On the other hand, there are few studies on the design and mechanical effects of the side piles of the station with PBA method at home and abroad.…”
Section: Introductionmentioning
confidence: 99%